Diagnostic performance of 68Ga-PSMA-11 PET/MRI-guided biopsy in patients with suspected prostate cancer: a prospective single-center study. - Ferraro, Daniela A.; Becker, Anton S.; Kranzbühler, Benedikt; Mebert, Iliana; Baltensperger, Anka; Zeimpekis, Konstantinos G.; Grünig, Hannes; Messerli, Michael; Rupp, Niels J.; Rueschoff, Jan H.; Mortezavi, Ashkan; Donati, Olivio F.; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2021)
Purpose: Ultrasound-guided biopsy (US biopsy) with 10–12 cores has a suboptimal sensitivity for clinically significant prostate cancer (sigPCa). If US biopsy is negative, magnetic resonance imaging (MRI)–guided biopsy is recommended, despite a low specificity for lesions with score 3–5 on Prostate Imaging Reporting and Data System (PIRADS). Screening and biopsy guidance using an imaging modality with high accuracy could reduce the number of unnecessary biopsies, reducing side effects. The aim of this study was to assess the performance of positron emission tomography/MRI with 68Ga-labeled prostate-specific membrane antigen (PSMA-PET/MRI) to detect and localize primary sigPCa (ISUP grade group 3 and/or cancer core length ≥ 6 mm) and guide biopsy. Methods: Prospective, open-label, single-center, non-randomized, diagnostic accuracy study including patients with suspected PCa by elevation of prostate-specific antigen (PSA) level and a suspicious lesion (PIRADS ≥3) on multiparametric MRI (mpMRI). Forty-two patients underwent PSMA-PET/MRI followed by both PSMA-PET/MRI-guided and section-based saturation template biopsy between May 2017 and February 2019. Primary outcome was the accuracy of PSMA-PET/MRI for biopsy guidance using section-based saturation template biopsy as the reference standard. Results: SigPCa was found in 62% of the patients. Patient-based sensitivity, specificity, negative and positive predictive value, and accuracy for sigPCa were 96%, 81%, 93%, 89%, and 90%, respectively. One patient had PSMA-negative sigPCa. Eight of nine false-positive lesions corresponded to cancer on prostatectomy and one in six false-negative lesions was negative on prostatectomy. Conclusion: PSMA-PET/MRI has a high accuracy for detecting sigPCa and is a promising tool to select patients with suspicion of PCa for biopsy. Trial registration: This trial was retrospectively registered under the name "Positron Emission Tomography/Magnetic Resonance Imaging (PET/MRI) Guided Biopsy in Men with Elevated PSA" (NCT03187990) on 06/15/2017 (https://clinicaltrials.gov/ct2/show/NCT03187990).